West-Eastern Divan Orchestra: A Representation of Peace Optimism from the Middle East - Selma Elfirda Karamy; Arry Bainus (Parahyangan Center for International Studies, 2020)
The high escalation of conflict that occurred in the Middle East region became a global issue which until now still has not found a solution. This situation is also complicated by the presence of US President Donald Trump's controversial immigration policy, which targets the Middle Eastern countries. Various efforts have been made by each country to reduce tension and maintain social and political stability in each country. In the midst of the many efforts made, emerging non-state actor that are trying to resolve conflicts, one of which is the Divan OrcThe high escalation of conflict that occurred in the Middle East region became a global issue which until now still has not found a solution. This situation is also complicated by the presence of US President Donald Trump's controversial immigration policy, which targets the Middle Eastern countries. Various efforts have been made by each country to reduce tension and maintain social and political stability in each country. In the midst of the many efforts made, emerging non-state actor that are trying to resolve conflicts, one of which is the Divan Orchestra, an international music organization that runs Music Diplomacy in the conflict countries. In this study, researchers will try to discuss The Divan Orchestra diplomatic roles as a representation of the message of peace from its members. The researcher will use the concepts of Music Diplomacy, Soft Power and Non-State Roles as Analysis Tools. While the research method used is a Qualitative Method using Literature Study. https://orcid.org/0000-0002-1953-7663